Internationalization of Born-Digital Firms: A Multi-Case Study of Indonesian Tech Unicorns - Putri, Novinda Krisna; Soelistyoningrum, Jenia Nur; Shakeel, Eram (Journal of Enterprise and Development (JED), 2025)
Purpose: This study investigates the mechanisms through which born-digital firms and technology companies enter international markets, utilizing the theoretical framework of the Uppsala internationalization model.Method: A qualitative multi-case study methodology was employed, incorporating secondary data sourced from corporate reports, industry news, and academic literature to analyze market entry modes, internationalization process strategies, and motivations for foreign market engagement.Result: The findings indicate that fintech companies such as Xendit and Kredivo adopt more cautious, regulation-driven strategies, often engaging in strategic partnerships and joint ventures. In contrast, digital firms like Gojek and Traveloka are inclined to pursue rapid and high-commitment internationalization through a combination of virtual presence and subsidiary offices. The study underscores the continued significance of psychic distance, as all firms initially expand into Southeast Asian markets that are geographically and culturally proximate.Practical Implications for Economic Growth and Development: The findings provide valuable insights for management regarding strategic decision-making in the internationalization process, highlighting the necessity for entry modes to be tailored to sector-specific contexts. The empirical results further demonstrate that successful internationalization requires a dual strategy that integrates virtual presence with localized approaches.Originality/Value: This study contributes to the existing literature by illustrating how born-digital firms are redefining traditional internationalization pathways, with particular emphasis on the roles of digital infrastructure, regulatory adaptation, and ecosystem integration in their foreign expansion endeavors.